COGNITIVE FEATURES OF DISCOURSE MARKERS AIMED AT REFORMULATING THOUGHT IN MODERN SPANISH LANGUAGE - Lomakina , Irina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with Spanish-language discourse markers aimed at reformulating the thought as a separate class of expressions and words that perform common functions: they connect fragments of discourse, explain what semantic links exist between the text elements, manage the communication process, the interpretation of discourse by the speaker and the recipient, correlate, compare and contrast statements in discourse. These units not only syntactically combine parts of the text, but also explain the cognitive connections between its parts, and can be aimed at reformulating the human thought. Communicative implicatures are blocked when the speaker realizes that his information has caused an undesirable effect in the mind of the interlocutor. The ability to understand this is determined as the theory of mind. An analysis of the cognitive functions of Spanish discourse markers aimed at reformulating the thought reveals that they aim to soften undesired statements or claims. DMs aimed at reformulating thought have their own program of functioning, according to which, they change the unwanted implicature that appeared in the previous statement, and on the other hand, they introduce a new block of discourse. With this new block, the communicator completes the information that the recipient should be left with. If we study the differences in the uses of DMs aimed at reformulating the thought, it is necessary to distinguish different shades of use within the limits of the above-mentioned algorithm. Awareness of these differences or shades of sense is usually inherent in native speakers and difficult to convey to those who are learning Spanish as a foreign language.___________References:• Lomakіna, І. «Semantiko-pragmatichnі osoblivostі diskursivnih markerіv u suchasnіj іspans'kіj movі [Semantic-pragmatic features of discourse markers in modern spanish language].» Problemi semantiki, pragmatiki ta kognіtivnoї lіngvіstiki [Problems of semantics, pragmatics and kognitive linguistics] 32 (2017) (In Ukr.).• Briz, A., Pons, S. y J., Portolés. Diccionario de partículas discursivas del español (2008), http://www.dpde.es• Escandell, Vidal, Leonetti,  «On the Rigidity of Procedural Meaning.» Procedural Meaning, Bingley, Emerald (2011): 81-102.• Martí Sánchez,  «Los marcadores discursivos para estudiantes y profesores.» Español como lengua extranjera. Actividades y claves realizadas por Sara Fernández Gómiz (Madrid: Edinumen, 2013).• Portolés, , Zorraquino, M. «Los marcadores del discurso.» (Madrid: Espasa Calpe, 1999), capítulo 63.• Nueva gramática de la lengua española, Real Academia española y asociación de academias de la lengua española (Madrid: Espasa, 2010_.• Schiffrin,  Discourse markers (Cambridge: Cambridge University Press, 1987), 364.
Keywords: дискурсивні маркери, що націлені на переоформлення думки, дискурс, когнітивні функції, іспанська мова, теорія розуму, імплікатура, комунікація